Early Impact of the Affordable Care Act Coverage Expansion on Safety‐Net Hospital Inpatient Payer Mix and Market Shares. (21st January 2018) - Wu, Vivian Y.; Fingar, Kathryn R.; Jiang, H. Joanna; Washington, Raynard; Mulcahy, Andrew W.; Cutler, Eli; Pickens, Gary
Abstract : Objective: To examine the impact of the Affordable Care Act's coverage expansion on safety‐net hospitals (SNHs). Study Setting: Nine Medicaid expansion states. Study Design: Differences‐in‐differences (DID) models compare payer‐specific pre‐post changes in inpatient stays of adults aged 19–64 years at SNHs and non‐SNHs. Data Collection Methods: 2013–2014 Healthcare Cost and Utilization Project State Inpatient Databases. Principal Findings: On average per quarter postexpansion, SNHs and non‐SNHs experienced similar relative decreases in uninsured stays (DID = –2.2 percent, p = .916). Non‐SNHs experienced a greater percentage increase in Medicaid stays than did SNHs (DID = 13.8 percent, p = .041). For SNHs, the average decrease in uninsured stays (–146) was similar to the increase in Medicaid stays (153); privately insured stays were stable. For non‐SNHs, the decrease in uninsured (–63) plus privately insured (–33) stays was similar to the increase in Medicaid stays (105). SNHs and non‐SNHs experienced a similar absolute increase in Medicaid, uninsured, and privately insured stays combined (DID = –16, p = .162). Conclusions: Postexpansion, non‐SNHs experienced a greater percentage increase in Medicaid stays than did SNHs, which may reflect patients choosing non‐SNHs over SNHs or a crowd‐out of private insurance. More research is needed to understand these trends.